Phytochemical analysis and effect of short-term administration of aqueous seed extract of Aframomum melegueta on haematologic indices of female albino rats - Uche Emmanuel Olunkwa (Shahrekord University of Medical Sciences, 2024)
Background and aims: Aframomum melegueta (Alligator pepper) is a dietary spice widely used for entertainment, religious rites, food flavor enhancer, possessing erythropoietic potentials, and many other medicinal uses. Women are included in eating this widely used spice. This experiment determined the health risk or benefit of short-term administration of aqueous seed extract of A. melegueta on haematologic indices of female albino rats. Methods: Thirty adult female albino rats weighing 160 to 200 g were used for the study. Male rats were introduced into the female rat cages of groups II-V within 12h at the expected estrous phase for mating and withdrawn afterward. Groups I, II, and III were orally administered distilled water only, while groups IV and V received oral doses of 5 µg/kg b.w. Cabergoline and 3000 mg/kg b.w. aqueous seed extract of A. melegueta respectively 24 hours postpartum and once daily by oral gavage for three days. Results: Fourier-transform infrared spectroscopy (FTIR) identified twelve functional groups in the seed extracts, namely -OH, -NH2 , CH, -NH3 +, -CH3 , -OH, -N=C=O, -C≡N, -C=C=C, -NH, -CH3 and -1,3,5-trisubstituted benzenes, while gas chromatography with flame ionization detector (GCFID) determined 15 bioactive components namely kaempferol, naringenin, Sapogernin, flavanones, anthocyanin, flavan-3-ol, cyanogenic glycoside, ribalinidine, rutin, catechin, resveratrol, spartein, epicatechin, steroid and phytate. Non-significant alterations in hemoglobin, packed cell volume (PCV), and red blood cell count were observed. There was a significant (P<0.05) decrease in WBC during pregnancy, but it was improved postpartum. However, platelet count was significantly (P<0.05) reduced after extract administration. Conclusion: The results indicate no adverse anemic condition elicited during pregnancy and delivery on haematologic parameters, namely red blood cells, hemoglobin, and PCV, with a significant decrease in WBC during pregnancy as well as reduction in platelet counts (thrombocytopenia) of extract treated animals post-partum likely due to the flavonoid, resveratrol as well as rutin and (-)-epicatechin components of A. melegueta and thus may increase the risk of bleeding disorders but reflects a positive anti-atherogenic and cardioprotective effect.